2008
DOI: 10.1016/j.ab.2007.10.025
|View full text |Cite
|
Sign up to set email alerts
|

A high performance gel filtration chromatography method for γ-glutamyltransferase fraction analysis

Abstract: The clinical relevance of serum gamma-glutamyltransferase (GGT) activity, in areas other than hepatic function, has recently been increased by several epidemiological associations. Still, GGT remains a nonspecific test because of the influence of various pathophysiological factors. We devised a procedure based on gel filtration chromatography, followed by postcolumn injection of fluorescent GGT substrate (gamma-glutamyl-7-amido-4-methylcoumarin), permitting the quantification of GGT fractions in serum or plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 26 publications
0
60
0
1
Order By: Relevance
“…Fractional GGT analysis was performed as previously described [27,28] using an FPLC (fast protein liquid chromatography) system (AKTA purifier, GE Healthcare Europe, Milan, Italy) equipped with a gel-filtration column (Superose 6 HR 10/300 GL, GE Healthcare Europe) and a fluorescence detector (Jasco FP-2020, Jasco Europe, Lecco, Italy). Plaque homogenates and plasma samples (0.02 ml) were injected in the gel-filtration column, after being filtered with a 0.45 mm polyvinylidene fluoride Millipore filter.…”
Section: Fractional Ggt Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Fractional GGT analysis was performed as previously described [27,28] using an FPLC (fast protein liquid chromatography) system (AKTA purifier, GE Healthcare Europe, Milan, Italy) equipped with a gel-filtration column (Superose 6 HR 10/300 GL, GE Healthcare Europe) and a fluorescence detector (Jasco FP-2020, Jasco Europe, Lecco, Italy). Plaque homogenates and plasma samples (0.02 ml) were injected in the gel-filtration column, after being filtered with a 0.45 mm polyvinylidene fluoride Millipore filter.…”
Section: Fractional Ggt Analysismentioning
confidence: 99%
“…The GGT activity has been hypothesized to exert a direct pro-oxidant activity, eliciting the production of reactive oxygen species from cystenylglycine (CysGly) moieties via its catalytic activity on extracellular glutathione [23e25], the occurrence of GGT-mediated redox reactions having been demonstrated within the plaque [26]. Recently, four plasma GGT fractions have been identified by molecular size exclusion chromatography, i.e., b-GGT, m-GGT and s-GGT (that very likely represent >2000, 940 and 140 kDa, respectively, lipoproteinbound molecular masses) plus the 70 kDa free fraction f-GGT [27,28]; only the highest molecular weight fraction b-GGT, has been found within atherosclerotic plaques by our group [26].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating GGT is supposed to originate mostly from the liver (12,13) and is influenced by genetic and environmental factors (14). Based on gel filtration chromatography, researchers from the Pisa University have identified 4 GGT fractions with different molecular weight in subjects of both sexes: big (b-GGT), medium (m-GGT), small (s-GGT) and free (f-GGT) (15). Recent studies have suggested that b-GGT consists of membrane microvesicles and it may serve as a precursor for smaller fractions (m-GGT and s-GGT) whereas f-GGT represents free soluble form of the enzyme (4).…”
Section: Figurementioning
confidence: 99%
“…We had exclude patients who were with liver disease and intestinal obstruction at the first time presented in our cancer center in order to limit the bias (He et al, 2013;He et al, 2013). Franzini had reported that there were at least four kinds of GGT, and b-GGT was produced other than liver (Franzini et al, 2008;Franzini et al, 2009), thus the subtypes of GGT may improve the specificity and severe as promising candidates in the further.…”
Section: Discussionmentioning
confidence: 99%
“…γ-glutamyl transpeptidase (GGT), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) which were included in biochemical test, were also showed as prognostic factors (Saif et al, 2005;Koukourakis et al, 2006;Pompella et al, 2006;Franzini et al, 2008;Franzini et al, 2009;Xie et al, 2014). However, previous studies had several drawbacks.…”
Section: Prognostic Model Built On Blood-based Biomarkers In Patientsmentioning
confidence: 99%